Anxiety, Depression and Quality of Life in Older Adults: Trajectories of Influence across Age - Ribeiro, Oscar (2021)
This study focuses on the influence of anxiety and depression on individual trajectories of quality of life in old age through a longitudinal approach. A representative sample of adults aged 50+ living in Portugal and participating in wave 4 (W4) and wave 6 (W6) of the Survey of Health, Ageing and Retirement in Europe (SHARE) project was considered. Participants, 1765 at baseline (W4) and 1201 at follow up (W6), were asked about their quality of life (CASP-12) and emotional status (Euro-D scale; five items from the Beck Anxiety Inventory). Linear Mixed Effects models were performed to identify factors associated with changes in quality of life across age. Increasing age was found to have a significant negative effect on quality of life. Lower education and higher levels of depression and anxiety at baseline were also associated with worse quality of life; 42.1% of the variation of CASP-12 across age was explained by fixed and random effects, being depression followed by anxiety as the factors that presented with the highest relative importance. Both depression and anxiety play an important role in quality of life in older adults and must be acknowledged as important intervention domains to foster healthy and active aging.